Combined effect of healthy lifestyles and obesity on cardiometabolic risks in Chinese rural adults - Hui Fan; Xingyu Zhang; Chongjian Wang; Chunlei Han (BMC Public Health)
Abstract Background Combined effect of healthy lifestyles and obesity on cardiometabolic risks were unclear in Chinese rural adults. We aimed to assess the above-mentioned issue. Methods This study included 25,123 adults from baseline survey of Henan rural cohort study. We collected information regarding current not smoking, current not drinking, healthy diet, adequate exercise, and healthy sleep. We calculated the number of healthy lifestyle factors for each participant or used the latent class analysis to identify clustering classes of healthy lifestyle. Body mass index (BMI), waist circumference (WC), blood pressure, blood lipid, and fasting blood glucose were measured. Logistic models were applied to assess the combined associations of healthy lifestyles and obesity with cardiometabolic risks. Results 3.8%, 45.8%, and 50.4% of all participants had 0–1, 2–3, and 4–5 healthy factors. The prevalence of obesity defined by BMI and WC was 17.1% and 38.1%, respectively. Compared with participants with obesity who met 0–1 healthy factor, those with obesity who met 4–5 healthy factors have a lower risk of hypertension (odds ratio [OR], 0.41; 95% confidence intervals [95%CI], 0.29–0.58) and dyslipidemia (OR, 0.49; 95%CI, 0.35–0.68) except hyperglycemia (OR, 0.87; 95%CI, 0.53–1.43). Irrespective of the healthy lifestyle scores, compared with participants with normal weight, those with obesity were at higher risk of hypertension, dyslipidemia and hyperglycemia. We obtained similar results when using the latent class analysis or WC to define obesity. Conclusion Our findings indicated that healthy lifestyle did not entirely offset the obesity-related cardiometabolic risks although it brought some benefits.